2021
DOI: 10.2337/dc21-0065
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Glucagon-Like Peptide 1 Receptor Agonist and Sodium–Glucose Cotransporter 2 Inhibitor Use and COVID-19 Outcomes

Abstract: To determine the respective associations of premorbid glucagon-like peptide-1 receptor agonist (GLP1-RA) and sodium-glucose cotransporter 2 inhibitor (SGLT2i) use, compared with premorbid dipeptidyl peptidase 4 inhibitor (DPP4i) use, with severity of outcomes in the setting of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. RESEARCH DESIGN AND METHODSWe analyzed observational data from SARS-CoV-2-positive adults in the National COVID Cohort Collaborative (N3C), a multicenter, longitudin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
60
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 40 publications
4
60
0
2
Order By: Relevance
“…Yet, there is still insufficient evidence to clarify the benefit of GLP-1RAs in patients with T2D and SARS-CoV2 infection, so far mainly limited to data obtained from retrospective analyses of few databases. In the US, the National COVID Cohort Collaborative (N3C) Consortium have performed the analysis of observational data from SARS-CoV-2-positive adults with a prescription for GLP1-RAs, sodium-glucose cotransporter 2 inhibitors (SGLT2i) inhibitors or dipeptidyl peptidase 4 inhibitors (DPP4i) within 24 months of positive SARS-CoV-2 PCR test [ 39 ]. Interestingly, the authors have very recently reported that premorbid GLP1-RAs and SGLT2i use, compared with DPP4i usage, was associated with lower odds of mortality and other adverse outcomes, such as emergency room visits and hospitalizations [ 39 ].…”
Section: Glp1-ras In Patients With T2d and Sars-cov2 Infectionmentioning
confidence: 99%
“…Yet, there is still insufficient evidence to clarify the benefit of GLP-1RAs in patients with T2D and SARS-CoV2 infection, so far mainly limited to data obtained from retrospective analyses of few databases. In the US, the National COVID Cohort Collaborative (N3C) Consortium have performed the analysis of observational data from SARS-CoV-2-positive adults with a prescription for GLP1-RAs, sodium-glucose cotransporter 2 inhibitors (SGLT2i) inhibitors or dipeptidyl peptidase 4 inhibitors (DPP4i) within 24 months of positive SARS-CoV-2 PCR test [ 39 ]. Interestingly, the authors have very recently reported that premorbid GLP1-RAs and SGLT2i use, compared with DPP4i usage, was associated with lower odds of mortality and other adverse outcomes, such as emergency room visits and hospitalizations [ 39 ].…”
Section: Glp1-ras In Patients With T2d and Sars-cov2 Infectionmentioning
confidence: 99%
“…The risks of hospital admission, ICU admission and mechanical ventilation were overall similar in DPP4i and GLP-1RAs users vs. SGLT2i users [ 47 ]. In addition, the recently published observational study from the National COVID Cohort Collaborative (N3C), including 12,446 SARS-CoV-2-positive adults, with 60-day mortality as primary outcome, showed that both GLP1-RAs and SGLT2i use were associated with lower 60-day mortality compared to DPP4i use [ 48 ].…”
Section: Use Of Dpp4i In Patients With T2dm and Covid-19mentioning
confidence: 99%
“…However, the risks of hospital admission, ICU admission and mechanical ventilation were overall similar for all of three studied drug classes [ 47 ]. The previously cited observational study showed that both GLP1-RAs and SGLT2i usage were associated with lower 60-day mortality in comparison to DPP4i usage [ 48 ]. Further, a Spanish multicentre observational study enrolling very old patients with T2DM and COVID-19 showed no association between preadmission use of SGLT2i and in-hospital mortality [ 34 ].…”
Section: Use Of Sglt2i In Patients With T2dm and Covid-19mentioning
confidence: 99%
See 1 more Smart Citation
“… 51 Overall, GLP‐1 RAs have been shown to exhibit anti‐inflammatory actions. 52 It should be noted that data from human studies on the effects of DPP4 inhibitors and GLP‐1 RAs on the incidence and treatment of COVID‐19 is limited to a few observational studies 45 , 53 , 54 , 55 but there are ongoing randomised clinical trials. 56 , 57 , 58…”
Section: Hypoglycaemic Agents and Covid‐19: Any Interactions?mentioning
confidence: 99%